Pengaruh Tipe Industri, Kinerja Lingkungan, Dan Profitabilitas Terhadap Carbon Emission Disclosure - Apriliana, Erika (WIDYAKALA: JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2019)
The purpose of this study was to examine the effect of Industrial Type, Environmental Performance, and Profitability on Carbon Emission Disclosure. The independent variable in this study is Industry Type which is measured using dummy variables, Environmental Performance is measured using PROPER and Profitability is measured using return on assets. Carbon Emission Disclosure as the dependent variable was measured using a checklist adopted from the research of Choi et al. The population of this study is non-financial companies registered in 2015-2017. By using purposive sampling method and obtained a total sample of 33 companies per year. The method of analysis of this study includes descriptive statistical analysis, classic assumption test, hypothesis testing and multiple linear regression. The results of this study indicate that Industry Type and Profitability have a significant effect on the level of carbon emissions disclosure. Meanwhile, Environmental Performance does not have a significant effect on the level of carbon emissions disclosure. Carbon Emission Disclosure variables can be explained by Industry Type, Environmental Performance and Profitability variables of 17.9%, while the remaining 82.1% are influenced by other variables not examined in this study.Keywords : Carbon Emission Disclosure, Voluntary Disclosures, Industrial Type, Environmental Performance, Profitability